2018
DOI: 10.1111/apt.14997
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: efficacy and safety of switching patients between reference and biosimilar infliximab

Abstract: Summary Background Biosimilar versions of widely prescribed drugs, including the tumour‐necrosis factor antagonist infliximab, are becoming increasingly available. As biosimilars are not identical copies of reference products, evidence may be required to demonstrate that switching between a reference biologic and biosimilars is safe and efficacious. To establish interchangeability, US Food and Drug Administration guidance states that studies must demonstrate that biosimilars remain equivalent or non‐inferior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 48 publications
1
62
0
3
Order By: Relevance
“…40 Overall, the evidence supports the safety and efficacy of a one-time switch between the RP and the infliximab biosimilar. 30 This is in line with recommendations recently published in a consensus document by multidisciplinary experts. 41 It should be mentioned that data on the safety and efficacy of switching from one biosimilar to another of the same originator or of multiple switches among different molecules are lacking.…”
Section: Infliximab Biosimilarssupporting
confidence: 86%
See 1 more Smart Citation
“…40 Overall, the evidence supports the safety and efficacy of a one-time switch between the RP and the infliximab biosimilar. 30 This is in line with recommendations recently published in a consensus document by multidisciplinary experts. 41 It should be mentioned that data on the safety and efficacy of switching from one biosimilar to another of the same originator or of multiple switches among different molecules are lacking.…”
Section: Infliximab Biosimilarssupporting
confidence: 86%
“…28,29 The US Food and Drug Administration (FDA) approval of two other infliximab biosimilars (SB2 and PF-06438179) and the approvals of NI-071 in Japan and BOW015 in India were also based on studies on rheumatoid arthritis. 30,31 CT-P13 remains the most widely studied biosimilar for IBD. 32 Is CT-P13 as Effective as the Reference Product in Patients with Inflammatory Bowel Disease?…”
Section: Infliximab Biosimilarsmentioning
confidence: 99%
“…The effectiveness and safety of biosimilars in IBD is well‐proven, but there remains a lack of knowledge about these data among patients, and this contributes to the nocebo effect . To minimise misconceptions, health‐care providers should adequately inform and educate their patients .…”
Section: Discussionmentioning
confidence: 99%
“…Data from the DANBIO registry of patients with inflammatory rheumatic disease demonstrated that a mandatory switch from reference infliximab to CT-P13 resulted in only minor changes to outpatient healthcare resource use [11], whereas a recent study found that the modest cost savings offered by biosimilar etanercept did not justify the additional workload involved in actively switching patients from the RP in some Swedish counties [162]. Data regarding single switches are accumulating, but, to our knowledge, no published studies have investigated cross-switching (between two biosimilars) or multiple/ repeated switches in RA or IBD [159,163,164] with regard to efficacy, safety, or cost considerations. However, evidence regarding multiple switching is emerging in psoriasis, with no impact on efficacy, safety, or immunogenicity detected after up to four switches between reference adalimumab and GP2017 [165] or up to three switches between reference etanercept and GP2015 [166].…”
Section: Pharmacoeconomists' Perspective: Cost Of and Access To Biolomentioning
confidence: 99%